Clinical progress in MSC-based therapies for the management of severe COVID-19. (December 2022) - Rossello-Gelabert, Maria; Gonzalez-Pujana, Ainhoa; Igartua, Manoli; Santos-Vizcaino, Edorta; Hernandez, Rosa Maria
Abstract: Considering the high impact that severe Coronavirus disease 2019 (COVID-19) cases still pose on public health and their complex pharmacological management, the search for new therapeutic alternatives is essential. Mesenchymal stromal cells (MSCs) could be promising candidates as they present important immunomodulatory and anti-inflammatory properties that can combat the acute severe respiratory distress syndrome (ARDS) and the cytokine storm occurring in COVID-19, two processes that are mainly driven by an immunological misbalance. In this review, we provide a comprehensive overview of the intricate inflammatory process derived from the immune dysregulation that occurs in COVID-19, discussing the potential that the cytokines and growth factors that constitute the MSC-derived secretome present to treat the disease. Moreover, we revise the latest clinical progress made in the field, discussing the most important findings of the clinical trials conducted to date, which follow 2 different approaches: MSC-based cell therapy or the administration of the secretome by itself, as a cell-free therapy. Highlights: Provide a comprehensive overview of the intricate inflammatory process derived from the immune dysregulation in COVID-19. Discuss the potential of the cytokines and growth factors that constitute MSC-derived secretome to treat the disease. Revise the latest clinical progress made in the field, discussing the most important findings conducted to date.